2018 Thales Data Threat Report: Retail Edition. Issue 8 (August 2018) - Unknown
Abstract : Data beaches among US retailers have more than doubled in the past year, according to research by Thales eSecurity. The retail edition of its latest threat report found that half of US retailers had experienced a data breach over the previous 12 months, compared with 19% the previous year.